The need for night admission to a Psychosocial Care Center: perceptions of drug users - Brandão, Thyara Maia; Breda, Mércia Zeviani; Santos, Débora de Souza; Albuquerque, Maria Cícera dos Santos (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
Objective: To apprehend the need for night admission as perceived by people attended to at a psychosocial Care Center for Alcohol and Other Drugs 24h. Method: qualitative approach, with participation of 12 users with experiences of nighttime admission to this service. Data were collected by interview, field diary and systematic observation. Content analysis of the thematic type was used to treat, categorize and interpret the information. Results: there was a perceived need for night admission due to the loss of control over drug use, damage caused by addiction, and difficulties in living on the street. Conclusion: individualized care should be the focus of nighttime admission and in other services of the Psychosocial Care Network.